Silk fibroin bone meal as well as preparation method and application thereof

Through spray drying and freeze-thaw cycle processing, silk fibroprotein bone meal with differentiated degradation rates and optimized pore structure was prepared, which solved the problems of high cost, single components and insufficient adhesion in the bone repair process of existing xenogeneic bone graft materials, and achieved efficient bone repair results.

CN119633171APending Publication Date: 2025-03-18YUEMEI BIOTECHNOLOGY (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938548.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing xenograft materials have high cost, single components, consistent degradation rate and insufficient adhesion during bone repair, which affect the rate and effect of bone repair.

Method used

The bone meal consisting of silk fibroin, hydroxyapatite and phosphate compounds was prepared by spray drying and freeze-thaw cycle treatment. By designing differentiated degradation rates and optimizing pore structure, the biocompatibility and adhesion properties of the materials were improved.

Benefits of technology

The spatial support and nutritional delivery during bone repair is achieved, which significantly improves the rate and effect of bone repair, reduces production costs, and enhances the ability to combine materials and tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633171A_ABST
    Figure CN119633171A_ABST
Patent Text Reader

Abstract

The invention discloses silk fibroin bone meal as well as a preparation method and application thereof. The preparation method comprises the following steps: preparing water-soluble silk fibroin powder by adopting a spray drying method; carrying out post-treatment on the water-insoluble silk fibroin to obtain water-insoluble silk fibroin powder; carrying out biomimetic mineralization in calcium salt by taking silk fibroin as a template to prepare hydroxyapatite particles; the preparation method comprises the following steps: dispersing hydroxyapatite particles and water-insoluble silk fibroin powder into a silk fibroin solution, performing freeze-thaw cycle treatment on the obtained mixed solution, and drying to obtain a silk fibroin blocky material; and grinding into powder, and mixing with water-soluble silk fibroin powder to obtain the silk fibroin bone meal. The silk fibroin bone meal provided by the invention has the advantages of simple components, no immunoreaction or toxic risk, adjustable shape, different degradation rates, controllable pore structure and better tissue binding ability, and can effectively improve the bone tissue repair efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a silk fibroin bone powder and a preparation method and application thereof. Background Art

[0002] In the field of dentistry, problems such as tooth loss, missing teeth, and structural abnormalities often stem from abnormal tooth development or poor eating habits, and are extremely common clinical conditions. In the process of treatment and restoration, in order to restore the patient's oral functionality and aesthetics, dental implants, as an advanced and effective treatment method, have become the first choice for many patients. However, in actual operations, some patients often have problems with insufficient bone mass, which is often caused by long-term tooth loss or periodontal disease before tooth extraction, which directly affects the successful implantation of the implant and its subsequent retention stability. As a key factor in the success of dental implant surgery, the integrity of the base bone is crucial to the long-term stability and function of the implant. In order to solve the problem of insufficient bone mass, bone augmentation surgery or maxillary sinus lift surgery is often used clinically to solve the problem, aiming to promote bone cell infiltration, blood vessel growth, and bone defect repair by implanting bone graft materials into the bone tissue loss area around the implant.

[0003] There are many kinds of bone transplant materials available, mainly including autologous bone, allogeneic bone, xenogeneic bone and synthetic bone. Among them, xenogeneic bone has been widely used in dental treatment due to its wide source and excellent biological properties. This type of material is usually made of calf bone by calcining into bone powder, which has controllable size and is easy to operate. However, the high cost, single composition and same degradation rate of xenogeneic bone make the bone repair process one-way and uncontrollable, which affects the rate and effect of bone repair to a certain extent. In addition, powdered xenogeneic bone transplant materials also have the problem of insufficient adhesion. In large bone defects, this type of material is difficult to combine firmly and stably, resulting in poor repair effect, and may even cause the transplant material to fall off or shift, further affecting the stability and success rate of the implant. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a silk fibroin bone powder and a preparation method and application thereof. The silk fibroin, which is widely available and low-cost, is used as the main component. The differentiated degradation rates of the components in the material are achieved through design, thereby providing spatial support and nutrient delivery for the bone repair process. At the same time, it exhibits excellent material and tissue adhesion properties at the defect site, further improving the bone repair rate and achieving excellent repair effect.

[0005] The present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing silk fibroin bone powder, comprising the following steps:

[0007] (1) preparing a water-soluble silk fibroin powder from a silk fibroin solution by a spray drying method; and subjecting the water-soluble silk fibroin powder to temperature control and high-pressure inert gas treatment to obtain a water-insoluble silk fibroin powder;

[0008] (2) mixing a phosphate compound and a silk fibroin solution to obtain a silk fibroin-phosphate mixed solution, adding the silk fibroin-phosphate mixed solution to a solution containing calcium ions, and centrifuging and drying the obtained precipitate to obtain hydroxyapatite particles;

[0009] (3) dispersing the hydroxyapatite particles obtained in step (2) and the water-insoluble silk fibroin powder obtained in step (1) in a silk fibroin solution, subjecting the obtained mixed solution to a freeze-thaw cycle, and obtaining a silk fibroin block material after drying;

[0010] (4) The silk fibroin block material obtained in step (3) is made into bone powder, and the bone powder is mixed with the water-soluble silk fibroin powder obtained in step (1) to obtain the silk fibroin bone powder.

[0011] Silk is a natural polymer protein fiber, the main component of which is silk fibroin, which accounts for about 75%, and has excellent immunogenicity and biocompatibility. The secondary structure of silk fibroin is often divided into two types, Silk I and Silk II, namely the crystalline and amorphous states. The regulation of these two structures is the key way to optimize the mechanical properties, degradation properties and other characteristics of silk fibroin materials. Silk fibroin not only has excellent and controllable mechanical properties, plasticity and biodegradability, but also can effectively promote the early and late expression of cell osteogenic markers, such as dwarf-related transcription factor 2, osteocalcin and osteomodulin mRNA. In addition, its side chain-rich carboxyl groups serve as mineralization sites for hydroxyapatite, further supporting cell growth and accelerating the healing process of bone defects.

[0012] Furthermore, the preparation method of the silk fibroin solution in the preparation method comprises the following steps:

[0013] S1. Immersing silk in a sodium carbonate aqueous solution, boiling the silk, taking it out for washing, and drying it to obtain degummed silk;

[0014] S2. Under the condition of 40-90° C. in a water bath, the degummed silk is dissolved in a lithium bromide aqueous solution, and the obtained mixed solution is dialyzed to obtain the silk fibroin solution.

[0015] Furthermore, in S1, the concentration of sodium carbonate in the sodium carbonate aqueous solution is 0.05-2wt%.

[0016] Furthermore, in S1, the water bath ratio of the silk and the sodium carbonate aqueous solution is 1 g: (30-100) mL.

[0017] Furthermore, in S1, the boiling time is 30-60 minutes.

[0018] Furthermore, in S1, the specific operation of the cleaning is: taking out the silk and scrubbing it with pure water, wringing out the water, and repeating this process multiple times.

[0019] Furthermore, in S2, the concentration of lithium bromide in the lithium bromide aqueous solution is 9-10M.

[0020] Furthermore, in S2, the water bath ratio of the degummed silk and the lithium bromide aqueous solution is 1 g:(3-10) mL.

[0021] Further, in S2, the degummed silk is dissolved in a lithium bromide aqueous solution, and stirred for 2-5 hours after dissolution.

[0022] Furthermore, in S2, the obtained mixed solution is divided into dialysis bags and dialyzed in a flowing water environment for 3-5 days to obtain a silk fibroin solution.

[0023] Furthermore, in step (1), the preparation method of the water-soluble silk fibroin powder comprises the following steps: feeding a silk fibroin solution with a concentration of 0.5-5wt% into a spray drying device, and drying at an inlet air temperature of 120-150°C to obtain the water-soluble silk fibroin powder.

[0024] Furthermore, in step (1), the particle size of the water-soluble silk fibroin powder is 0.25-0.8 mm.

[0025] The main secondary structure of water-soluble silk fibroin powder is random coil and α-helix. It is directly mixed as a component without any post-processing. It dissolves quickly in bone powder after contact with blood, increasing the bonding between the material and tissue, and is conducive to the fixation of bone powder at the wound.

[0026] Furthermore, in step (1), the preparation method of the water-insoluble silk fibroin powder comprises the following steps: freezing the water-soluble silk fibroin powder at -80°C to -20°C for 6-72 hours, then raising the temperature to -10°C to -1°C within 12-48 hours and treating it for 2-48 hours, placing the treated powder in a high-pressure gas reaction device, evacuating the device and then introducing an inert gas at a pressure of 2-10MPa for 20-60 minutes to obtain the water-insoluble silk fibroin powder.

[0027] Furthermore, the inert gas may be nitrogen, argon, etc.

[0028] After treatment, the water-insoluble silk fibroin powder generates a Silk I structure, which, as a bone powder component, begins to degrade about 2-4 weeks after being implanted in the defect site. After degradation, gaps are generated to promote blood flow and tissue growth.

[0029] Furthermore, in step (2), the solution containing calcium ions is a calcium hydroxide solution and / or a calcium salt solution, such as a calcium chloride solution, a calcium nitrate solution, etc.

[0030] Furthermore, in step (2), the phosphoric acid compound is phosphoric acid and / or phosphate, such as dipotassium hydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, etc.

[0031] Furthermore, in step (2), the molar ratio of calcium ions to phosphate compounds is (1.5-2):1.

[0032] Furthermore, in step (2), the concentration of silk fibroin in the silk fibroin solution is 1-6 wt %.

[0033] In a specific embodiment, in step (2), the solution containing calcium ions is placed on a stirrer at 70-75° C. and kept in a stirring state, and a silk fibroin-phosphoric acid mixed solution is added dropwise to the solution containing calcium ions at an injection rate of 1-4 mL / min using a microinjection pump. After the reaction is completed, the precipitate generated in the solution is centrifuged at a speed of 8000-10000 r / min for 10-25 min, and the hydroxyapatite particles are obtained after washing and drying.

[0034] The hydroxyapatite particles prepared by the present invention are coated with silk fibroin, which can improve the mechanical properties of the material, provide space and mechanical support for bone repair while promoting bone repair, and the silk fibroin itself can serve as a hydroxyapatite deposition site, promoting hydroxyapatite deposition and thus further improving the bone repair rate.

[0035] Furthermore, in step (3), the mass ratio of the hydroxyapatite particles, the water-insoluble silk fibroin powder and the silk fibroin solution is (20-60):(30-70):(5-10).

[0036] Furthermore, in step (3), the concentration of silk fibroin in the silk fibroin solution is 1-6 wt %.

[0037] Furthermore, in step (3), the specific operation of the freeze-thaw cycle treatment is: pouring the obtained mixed solution into a mold, placing it at -80°C to -20°C for 8-24 hours, and then thawing it at 4-6°C for 12-48 hours, and repeating 1-5 cycles.

[0038] During the repeated freezing and thawing process, the low temperature causes the generated ice crystals to squeeze the silk protein molecules, thereby increasing the concentration and the compact structure of the molecular chains, prompting the polymer chains to be rearranged. The small void structures generated by repeated freezing and thawing are interspersed with the large holes formed after the sublimation of ice crystals.

[0039] Furthermore, in step (3), after the freeze-thaw cycle treatment, the sample is placed in a freeze dryer for 48-72 hours to obtain a silk fibroin block material.

[0040] Furthermore, in step (4), the specific method of preparing bone powder from the silk fibroin block material is as follows: placing the silk fibroin block material in a grinder, mechanically grinding and crushing it at 50-60 rad / min, and sieving to obtain bone powder with a particle size of 0.25-0.8 mm.

[0041] Furthermore, in step (4), the mass ratio of the water-soluble silk fibroin powder to the bone powder is (2-10):(90-98).

[0042] The present invention protects the silk fibroin bone powder prepared by the above method.

[0043] The present invention uses silk (such as mulberry silk) as the main raw material to prepare silk fibroin bone powder, wherein component 1 is water-soluble silk fibroin obtained by spray drying, and the main secondary structure is random coil and / or α-helix; component 2 is water-insoluble silk fibroin obtained by temperature regulation and high-pressure inert gas treatment of water-soluble silk fibroin, which gradually begins to degrade in about 2-4 weeks, and after degradation, holes of different sizes and arrangements are generated inside the material, which can allow blood flow and tissue growth; component 3 is hydroxyapatite prepared with silk fibroin as a template, which is the main component of bones, and can promote bone tissue repair while providing mechanical support and space required for tissue recovery for transplant materials at the defect. Component 2 and component 3 are repeatedly frozen and thawed after mixing with a silk fibroin solution, and a silk fibroin block material with a structure of coexistence of macropores and micropores is formed after drying, and then a powdered raw material is obtained by grinding and sieving, and the powdered raw material is mixed with component 1 according to different mass ratios to obtain the silk fibroin bone powder.

[0044] The present invention also protects the application of the silk fibroin bone powder as bone grafting material in oral implant surgery.

[0045] In practical applications, the shape and size of the silk fibroin bone powder provided by the present invention can be flexibly adjusted according to actual needs, and the powdered silk fibroin bone powder can be pressed into blocks, which not only maintains its original excellent performance but also has better structural stability and support.

[0046] Beneficial effects of the present invention:

[0047] 1. The silk fibroin bone powder provided by the present invention has simple ingredients and does not contain complex additives and toxic ingredients, thereby ensuring the safety and biocompatibility of the material and reducing the risk of immune response or toxicity that may be induced in practical applications.

[0048] 2. Compared with traditional animal bone materials, the material of the present invention does not require complicated processing steps, the preparation method is relatively simple, the production cost is effectively reduced, and it is suitable for mass production.

[0049] 3. The silk fibroin bone powder provided by the present invention can not only provide suitable mechanical properties to support and stabilize damaged tissues, but also provide suitable growth space and nutrient delivery channels for tissue healing through different degradation rates of each component and optimized pore structure, thereby improving the efficiency of bone tissue repair.

[0050] 4. The addition of water-soluble silk fibroin in the present invention significantly enhances the bonding ability between the implant material and the tissue. The introduction of water-soluble silk fibroin not only improves the surface properties of the material, but also promotes the adhesion and proliferation of cells on the surface of the material, thereby further improving the bone repair effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is the SEM image of the silk fibroin block material in Example 1.

[0052] Figure 2 This is a physical picture of the silk fibroin bone powder prepared in Example 1. DETAILED DESCRIPTION

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0054] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0055] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0056] In the following examples and comparative examples, the silk fibroin solution was prepared by the following method:

[0057] S1. The silk was immersed in a 1wt% sodium carbonate aqueous solution, wherein the water bath ratio of the silk and the sodium carbonate aqueous solution was 1g:100mL, and the silk was taken out after boiling for 30min, and washed with pure water for 3 times, and the water was wrung out, and the washing-wringing step was repeated 3 times, and the silk was dried at 60°C for 48h to obtain degummed silk;

[0058] S2. Under 65°C water bath conditions, the degummed silk was dissolved in 9.3M lithium bromide aqueous solution, wherein the water bath ratio of the degummed silk and the lithium bromide aqueous solution was 1g:5mL, and the obtained mixed solution was divided into dialysis bags and dialyzed in a flowing water environment for 3 days to obtain the silk fibroin (SF) solution.

[0059] Example 1

[0060] A method for preparing silk fibroin bone powder comprises the following steps:

[0061] (1) Add 20 mL of 0.06 M H 3 PO 4 The solution was mixed evenly with 4 g of 2.5 wt% silk fibroin solution to obtain a silk fibroin-phosphoric acid mixed solution. 100 mL of 0.02 M Ca(OH) 2 The aqueous solution was placed on a stirrer at 70°C to maintain stirring, and a microinjection pump was used to inject Ca(OH) 2 The silk fibroin-phosphoric acid mixed solution was added dropwise into the aqueous solution. After the reaction was completed, the precipitate generated in the solution was centrifuged at a speed of 9000 r / min for 20 minutes, washed three times with ultrapure water, and then dried to obtain hydroxyapatite particles.

[0062] (2) The 1.5 wt% silk fibroin aqueous solution is fed into a spray drying device and dried at an inlet air temperature of 120° C. to obtain the water-soluble silk fibroin powder, which is sieved to obtain a water-soluble silk fibroin powder with a particle size of 0.25 mm for later use. The water-soluble silk fibroin powder is frozen at -50° C. for 24 hours, then the temperature is raised to -6° C. within 30 hours and maintained for 48 hours, and the treated powder is placed in a high-pressure gas reaction device, and nitrogen is introduced after vacuuming, with a pressure of 10 MPa, and maintained for 40 minutes to obtain the water-insoluble silk fibroin powder.

[0063] (3) The hydroxyapatite particles and the water-insoluble silk fibroin powder obtained in step (1) are dispersed in a 3 wt % silk fibroin solution, wherein the mass ratio of the hydroxyapatite particles, the water-insoluble silk fibroin powder and the silk fibroin solution is 39:52:9. The obtained mixed solution is poured into a cylindrical mold with a diameter of 1.5 cm and a height of 2.5 cm, and placed at -50°C for 24 h, and then thawed at 4°C for 24 h, and repeated for 3 cycles. After the freeze-thaw cycle is completed, the mixture is placed in a freeze dryer for freeze drying for 48 h to obtain a silk fibroin block material. The morphology of the silk fibroin block material in Example 1 is characterized by a scanning electron microscope (SEM). The characterization results are shown in FIG. Figure 1 As shown, the silk fibroin block material has a pore structure with interpenetrating and interconnected pores of varying sizes.

[0064] (4) The silk fibroin block material is placed in a grinder, and mechanically ground and crushed for 12 hours at 60 rad / min, and sieved to obtain bone powder with a particle size of 0.25 mm. The bone powder is mixed with water-soluble silk fibroin powder, wherein the mass ratio of water-soluble silk fibroin powder to bone powder is 3:97, to obtain the silk fibroin bone powder, as shown in the actual picture. Figure 2 shown.

[0065] Example 2

[0066] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that: in step (2), the water-soluble silk fibroin powder is freeze-dried at -50°C for 24 hours, and then the temperature is raised to -6°C within 30 hours and maintained for 24 hours to obtain the water-insoluble silk fibroin powder.

[0067] Example 3

[0068] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that: in step (3), the material is placed at -20°C for 24 hours, then thawed at 4°C for 24 hours, and the cycle is repeated three times. After the freeze-thaw cycle is completed, the material is placed in a freeze dryer and freeze-dried for 48 hours to obtain a silk fibroin block material.

[0069] Example 4

[0070] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that: in step (3), the material is placed at -80°C for 24 hours, then thawed at 4°C for 24 hours, and the cycle is repeated three times. After the freeze-thaw cycle is completed, the material is placed in a freeze dryer and freeze-dried for 48 hours to obtain a silk fibroin block material.

[0071] Example 5

[0072] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (3), the mass ratio of hydroxyapatite particles, water-insoluble silk fibroin powder and silk fibroin solution is 45:47:8.

[0073] Example 6

[0074] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (3), the mass ratio of hydroxyapatite particles, water-insoluble silk fibroin powder and silk fibroin solution is 51:42:7.

[0075] Example 7

[0076] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (3), the mass ratio of hydroxyapatite particles, water-insoluble silk fibroin powder and silk fibroin solution is 45:47:8.

[0077] Example 8

[0078] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (3), the mass ratio of hydroxyapatite particles, water-insoluble silk fibroin powder and silk fibroin solution is 51:42:7.

[0079] Example 9

[0080] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (3), the mass ratio of hydroxyapatite particles, water-insoluble silk fibroin powder and silk fibroin solution is 45:47:8.

[0081] Example 10

[0082] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (3), the mass ratio of hydroxyapatite particles, water-insoluble silk fibroin powder and silk fibroin solution is 51:42:7.

[0083] Comparative Example 1

[0084] A method for preparing silk fibroin bone powder comprises the following steps:

[0085] (1) Add 20 mL of 0.06 M H 3 PO 4 The solution was mixed evenly with 4 g of 2.5 wt% silk fibroin solution to obtain a silk fibroin-phosphoric acid mixed solution. 100 mL of 0.02 M Ca(OH) 2 The aqueous solution was placed on a stirrer at 70°C to maintain stirring, and a microinjection pump was used to inject Ca(OH) 2 The silk fibroin-phosphoric acid mixed solution was added dropwise into the aqueous solution. After the reaction was completed, the precipitate generated in the solution was centrifuged at a speed of 9000 r / min for 20 minutes, washed three times with ultrapure water, and then dried to obtain hydroxyapatite particles.

[0086] (2) The 1.5 wt% silk fibroin aqueous solution is fed into a spray drying device and dried at an inlet air temperature of 120° C. to obtain the water-soluble silk fibroin powder, which is sieved to obtain a water-soluble silk fibroin powder with a particle size of 0.25 mm for later use. The water-soluble silk fibroin powder is frozen at -50° C. for 24 hours, then the temperature is raised to -6° C. within 30 hours and maintained for 48 hours, and the treated powder is placed in a high-pressure gas reaction device, and nitrogen is introduced after vacuuming, with a pressure of 10 MPa, and maintained for 40 minutes to obtain the water-insoluble silk fibroin powder.

[0087] (3) The hydroxyapatite particles and water-insoluble silk fibroin powder obtained in step (1) are dispersed in a 3 wt % silk fibroin solution, wherein the mass ratio of the hydroxyapatite particles, the water-insoluble silk fibroin powder and the silk fibroin solution is 39:52:9, and the obtained mixed solution is poured into a cylindrical mold with a diameter of 1.5 cm and a height of 2.5 cm, and placed at -50°C for 24 h, and then thawed at 4°C for 24 h, and repeated for 3 cycles. After the freeze-thaw cycle is completed, the mixture is placed in a freeze dryer for freeze drying for 48 h to obtain a silk fibroin block material.

[0088] (4) placing the silk fibroin block material in a grinder, grinding and crushing it mechanically at 60 rad / min for 12 h, and sieving to obtain bone powder with a particle size of 0.25 mm, i.e., silk fibroin bone powder.

[0089] The silk fibroin bone powder prepared in Comparative Example 1 does not contain water-soluble silk fibroin components, and the ability of the material to bind to tissues is weakened, which is not conducive to the attachment and fixation of the material to the affected area.

[0090] Comparative Example 2

[0091] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (2), 99% ethanol solution is used to make water-soluble silk fibroin insoluble to obtain the water-insoluble silk fibroin powder.

[0092] The degradation time of the silk fibroin bone powder prepared in Comparative Example 1 was prolonged and single, and there was no different degradation rate to provide space and mechanical support for tissue growth.

[0093] Comparative Example 3

[0094] A method for preparing silk fibroin bone powder is basically the same as that of Example 1, except that in step (3), no freeze-thaw cycle treatment is performed.

[0095] The silk fibroin bone powder prepared in Comparative Example 3 has a single pore structure, and no small pores are formed on the macropore walls formed during freeze-drying. After grinding, there are fewer micropores in the silk fibroin bone powder, which affects cell infiltration and nutrient transport.

[0096] Test Example 1

[0097] The characteristic peaks of the silk fibroin bone powder prepared in Example 1, Example 2 and Comparative Example 2 were characterized by Fourier transform infrared spectrometer, and the content of β-turn protein in each group was calculated by peak fitting. The test results are shown in Table 1:

[0098] Table 1

[0099] sample β-turn protein content (%) Example 1 51.7 Example 2 44.3 Comparative Example 2 /

[0100] The higher the content of β-turn structural protein, the more silk fibroin content representing the Silk I structure. As can be seen from Table 1, the silk fibroin bone powder prepared by the present invention can adjust the Silk I structure content by changing the temperature and time during the freezing process, thereby adjusting the degradation rate of the bone powder. The shorter the heating treatment time, the lower the Silk I structure content in the bone powder and the faster the degradation rate.

[0101] Test Example 2

[0102] The pore sizes of the silk fibroin bone powder prepared in Example 1, Example 3, Example 4 and Comparative Example 3 were tested using a scanning electron microscope. Five points were taken from each group and the average value was taken. The test results are shown in Table 2:

[0103] Table 2

[0104] sample Average pore size (μm) Example 1 251.98±1.50 Example 3 228.28±1.03 Example 4 273.73±1.18 Comparative Example 3 204.16±2.07

[0105] The test results show that the freeze-thaw temperature affects the pore size of silk fibroin bone powder. A higher freezing temperature reduces the pore size of the material, making the prepared material more compact and improving the mechanical properties of the material.

[0106] Test Example 3

[0107] The compression performance of the silk fibroin bone powder prepared in Example 1, Examples 3-10 and Comparative Example 3 was tested using an Instron 8511 material testing machine. The testing method was as follows: the silk fibroin bone powder was pressurized to form a block and then cut into a sample with a specification of approximately 2×2 cm discs. The compressive capacity of each group of samples was tested at a loading speed of 10 mm / min. Five samples were tested in each group under the same conditions.

[0108] The test results are shown in Table 3:

[0109] Table 3

[0110]

[0111]

[0112] The test results show that the freeze-thaw temperature and the proportion of hydroxyapatite affect the mechanical properties of silk fibroin bone powder at the same time. The silk fibroin bone powder prepared in Example 8 has the best mechanical properties, and the compressive strength of the silk fibroin bone powder prepared in other embodiments is also greater than 5MPa, which can meet the requirements of bone mechanical properties of non-load-bearing parts within the range. The smaller the pore size and the higher the proportion of hydroxyapatite, the better the mechanical properties. The mechanical properties of the silk fibroin bone powder of Comparative Example 3 without freeze-thaw treatment are the best, but there is no pore structure with interlaced sizes, which is not conducive to angiogenesis and new bone reconstruction, and the biodegradability is poor.

[0113] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing silk fibroin bone powder, characterized in that: The following steps are involved: (1) preparing a water-soluble silk fibroin powder from a silk fibroin solution by a spray drying method; and subjecting the water-soluble silk fibroin powder to temperature control and high-pressure inert gas treatment to obtain a water-insoluble silk fibroin powder; (2) mixing a phosphate compound and a silk fibroin solution to obtain a silk fibroin-phosphate mixed solution, adding the silk fibroin-phosphate mixed solution to a solution containing calcium ions, and centrifuging and drying the obtained precipitate to obtain hydroxyapatite particles; (3) dispersing the hydroxyapatite particles obtained in step (2) and the water-insoluble silk fibroin powder obtained in step (1) in a silk fibroin solution, subjecting the obtained mixed solution to a freeze-thaw cycle, and obtaining a silk fibroin block material after drying; (4) The silk fibroin block material obtained in step (3) is made into bone powder, and the bone powder is mixed with the water-soluble silk fibroin powder obtained in step (1) to obtain the silk fibroin bone powder.

2. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the water-soluble silk fibroin powder comprises the following steps: feeding a silk fibroin solution with a concentration of 0.5-5wt% into a spray drying device, and drying at an inlet air temperature of 120-150°C to obtain the water-soluble silk fibroin powder.

3. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the water-insoluble silk fibroin powder comprises the following steps: freezing the water-soluble silk fibroin powder at -80°C to -20°C for 6-60h, then raising the temperature to -10°C to -1°C within 12-48h and treating it for 2-48h, placing the treated powder in a high-pressure gas reaction device, evacuating the device and introducing an inert gas at a pressure of 2-10MPa for 20-60min to obtain the water-insoluble silk fibroin powder.

4. The preparation method according to claim 1, characterized in that: In step (2), the solution containing calcium ions is placed on a stirrer at 70-75° C. and kept in a stirring state. A silk fibroin-phosphoric acid mixed solution is added dropwise to the solution containing calcium ions at an injection rate of 1-4 mL / min using a microinjection pump. After the reaction is completed, the precipitate generated in the solution is centrifuged at a speed of 8000-10000 r / min for 10-25 min, and the hydroxyapatite particles are obtained after washing and drying.

5. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the hydroxyapatite particles, the water-insoluble silk fibroin powder and the silk fibroin solution is (20-60):(30-70):(5-10).

6. The preparation method according to claim 1, characterized in that: In step (3), the concentration of silk fibroin in the silk fibroin solution is 1-6 wt %.

7. The preparation method according to claim 1, characterized in that: In step (3), the specific operation of the freeze-thaw cycle treatment is: pouring the obtained mixed solution into a mold, placing it at -80°C to -20°C for 8-24 hours, and then thawing it at 4-6°C for 12-48 hours, and repeating 1-5 cycles.

8. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the water-soluble silk fibroin powder to the bone powder is (2-10):(90-98).

9. Silk fibroin bone powder prepared by the method according to any one of claims 1 to 8.

10. Use of the silk fibroin bone powder according to claim 9 as bone grafting material in oral implant surgery.